2014
DOI: 10.1039/c4ob01483a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient cobalt-catalyzed C–N cross-coupling reaction between benzamide and aryl iodide in water

Abstract: A practical and efficient strategy for the N-arylation of benzamide catalysed by a Co(C2O4)·2H2O/dmeda system in water is reported. Under the optimized conditions, a wide variety of N-arylated products were obtained in good yields (up to 92%) using substituted aryl iodides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…In catalysing aryl C-N coupling, the desire for environmentally friendlier reagents and to alleviate some shortcomings of the coupling strategies mentioned above has prompted chemists to seek alternative catalysts that involve the use of NHC-based complexes of environmentally benign metals like iron [18] and nickel [19]. Despite the rapid progress made in the use of cobalt and its salts as catalysts for C-C coupling reactions [20], the application of catalyst systems containing Co in aryl amination are quite rare [21] and to the best of our knowledge those containing pincer NHCCo complexes have not been reported. Very recent work by Tan and Teo [21] has reported a M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…In catalysing aryl C-N coupling, the desire for environmentally friendlier reagents and to alleviate some shortcomings of the coupling strategies mentioned above has prompted chemists to seek alternative catalysts that involve the use of NHC-based complexes of environmentally benign metals like iron [18] and nickel [19]. Despite the rapid progress made in the use of cobalt and its salts as catalysts for C-C coupling reactions [20], the application of catalyst systems containing Co in aryl amination are quite rare [21] and to the best of our knowledge those containing pincer NHCCo complexes have not been reported. Very recent work by Tan and Teo [21] has reported a M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Despite the rapid progress made in the use of cobalt and its salts as catalysts for C-C coupling reactions [20], the application of catalyst systems containing Co in aryl amination are quite rare [21] and to the best of our knowledge those containing pincer NHCCo complexes have not been reported. Very recent work by Tan and Teo [21] has reported a M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial study began with the application of the previously reported conditions for the cobalt-catalyzed N-arylation 15 towards the cross-coupling of iodobenzene and 2-pyrrolidinone. To our delight, a modest yield of 50% of Narylated product was obtained ( Table 1, entry 1).…”
mentioning
confidence: 99%